Mono-, multi-, inter-, and transdisciplinarity in sport performance support teams: definitions and objectives - Hydes, S.; Strafford, B. W.; Stone, J. A.; Rothwell, M.; Davids, K. (Sports Coaching Review, 2026)
Growth in sport science disciplines, specialist coaching, and performance support roles is increasingly emphasised in research and applied practice to enhance athlete preparation and development. However, monodisciplinary, multidisciplinary, interdisciplinary, and transdisciplinary are used ambiguously and interchangeably across literature and within sporting organisations, blurring differences in how collaboration and integration may be operationalised. We examine these approaches, distinguishing their purpose, process, and collaboration and integration. Drawing on research and examples from high-performance sport, we propose clear, practice-oriented definitions and identify characteristics associated with each approach. We position transdisciplinarity as a problem-focused approach that could frame communication, collaboration, and integration of ideas around a performance challenge. To illustrate how these distinctions can be operationalised, a case exemplar demonstrates how a Department of Methodology (DoM) and unified game model could organise diverse expertise. By clarifying terminology and illustrating relevance, this paper aims to support intentional and coherent collaborative practice within high-performance sport environments.